A Vulnerability Assessment for a Future HIV Outbreak Associated With Injection Drug Use in Illinois, 2017–2018 - Bergo, Cara Jane; Epstein, Jennifer R.; Hoferka, Stacey; Kolak, Marynia Aniela; Pho, Mai T. (Frontiers in Sociology, 2021)
The current opioid crisis and the increase in injection drug use (IDU) have led to outbreaks of HIV in communities across the country. These outbreaks have prompted country and statewide analysis into identifying factors to determine areas at risk of a future HIV outbreak. Based on methodology used in a prior nationwide, county-level analysis by the US Centers for Disease Control, we examined Illinois at the ZIP code level (n=1383). Combined acute and chronic hepatitis C viral (HCV) infection among persons less than 40 years of age was used as an outcome proxy measure for IDU. Local and statewide data sources were used to identify predictors that are potentially predictive of high risk for HIV/ HCV transmission that fell within three main groups: health outcomes; access/ resources; and social /economic/ physical environment. A multivariable negative binomial regression was performed with population as an offset. The vulnerability score for each ZIP code was created using the final regression model that consisted of eleven factors, six risk factors and five protective factors. ZIP codes identified with the highest vulnerability ranking (top 10%) were distributed across the state yet focused in the rural southern region. The most populous county, Cook County, had only one vulnerable ZIP code. This analysis reveals more areas vulnerable to future outbreaks compared to past national analyses and provides more precise indications of vulnerability at the ZIP code level. The ability to assess risk at the ZIP code level allows local jurisdictions to more finely tune surveillance and preventive measures and target activities in these high-risk areas. The final model contained a mix of protective and risk factors revealing a heightened level of complexity underlying the relationship between characteristics that impact HCV risk. Following this analysis, Illinois prioritized recommendations to include increasing access to harm reduction services, specifically sterile syringe services, naloxone access, infectious disease screening and increased linkage to care for HCV and opioid use disorder.